Using coloured Petri nets to investigate fleet cannibalisation - Sheng, Jingyu; Prescott, Darren (Comadem International, 2015)
Cannibalisation is a maintenance activity that involves removing serviceable parts from inoperative platforms to replace unserviceable parts of the same type in other platforms. It can provide a significant benefit to fleet readiness, particularly if spare parts are in short supply. However, cannibalisation also has drawbacks: it brings an increased workload for maintenance crews and parts can be damaged during the cannibalisation process. For this reason, it is important to have a clear understanding of the effects that cannibalisation will have on fleet operation and maintenance. Accurate models are needed to predict the effects of cannibalisation on fleet performance and to provide fleet managers with trustworthy information on which to base maintenance decisions relating to cannibalisation and spare parts provision. This paper presents a coloured Petri net (CPN) model of fleet cannibalisation that takes account of fleet operation and a number of factors relating to maintenance. An example fleet is modelled and measures of average fleet readiness and maintenance cost are used to evaluate the effects of cannibalisation on fleet performance. The model is used to assess the impact of a number of maintenance factors and fleet size on the use of cannibalisation and fleet performance.